1990
DOI: 10.1073/pnas.87.17.6868
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of a single amino acid (aspartic acid for histidine) converts the functional activity of human complement C4B to C4A.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 35 publications
1
46
1
Order By: Relevance
“…Ester bonds are sensitive to hydroxylamine treatment whereas amide bonds are resistant (Carroll et al, 1990). dS.K.A.…”
Section: The Autolytic Cleavage Reactionmentioning
confidence: 99%
“…Ester bonds are sensitive to hydroxylamine treatment whereas amide bonds are resistant (Carroll et al, 1990). dS.K.A.…”
Section: The Autolytic Cleavage Reactionmentioning
confidence: 99%
“…A His residue in the ␣ chain at position 1106 imparts to C4B the ability to form ester linkages. The presence of an Asp residue at position 1106 results in C4A functionality and preferential amide bond formation with target ONH 2 groups (56). Differences in the binding properties of C4A (amide) and C4B (ester) may have important functional consequences.…”
Section: Activation Of the Complement Systemmentioning
confidence: 99%
“…Using site-directed mutagenesis at the cDNA level followed by expression of the modified proteins, it was found that the key residue lies in position 1106. The His at this position is crucial in conferring C4B-like binding acitivity whereas an Asp, Asn or Ala at this position renders the protein C4A-like [9,10]. Based on these observations, it was argued that the His of C4B plays a role in catalyzing the reaction of the thioester with hydroxyl groups on water and other compounds; thus, its reaction with amino groups is apparently less effective.…”
Section: Introductionmentioning
confidence: 99%